A Study on the Influencing Factors and Optimization Design of Combined Push-Pull Magnetic Drive Coupling. (2nd June 2019) - Zhenjun, Gao; Chaoqun, Hu; Feng, Hong; Jianrui, Liu; Huashan, Su
Abstract : In order to study the effect of geometrical parameters of magnetic drive coupling on magnetic torque and magnetic eddy current loss, based on the basic theory of electromagnetic field, the influence factors of magnetic performance of combined push-pull magnetic drive coupling are analyzed and optimized by means of finite element numerical calculation and orthogonal experiment. The optimal geometrical parameter scheme of magnetic drive coupling was obtained, and the magnetic performance of the optimal geometrical parameter model was studied experimentally. The geometrical parameters of the optimal scheme of magnetic drive coupling are internal radius of magnet r = 80 mm, thickness of permanent magnet t m = 8 mm, axial length L b = 144 mm, and thickness of yoke iron t i = 10 mm. The research shows that the optimization design method proposed in this paper is reliable in the design of magnetic drive coupling and can provide some theoretical reference for the design of magnetic drive coupling and the optimization of magnetic torque and magnetic eddy current loss.